Implementation of Inclusive Education at Muhammadiyah 1 Krian Elementary School in Implementing the Independent Curriculum P5 Program - Tirtoni, Feri; Novianti, Amelia Puja; A’yun, Amalia Qurrotul; Pramila, Riswanda Apri; Putri, Amalia Habibah Eka Nur (Universitas Muhammadiyah Sidoarjo, 2024)
This research aims to evaluate the implementation of inclusive education at the Muhammadiyah 1 Krian elementary school in the Implementation Program of the Strengthening Pancasila Student Profile (P5) Project in the Independent Curriculum. The Merdeka Curriculum, which emphasizes flexibility and developing students' individual potential, includes P5 as an effort to shape students' character and competencies according to Pancasila values. Inclusive education focuses on engaging all students, including those with special needs, in the same learning activities. The research method used was qualitative with a case study approach at SD Muhammadiyah 1 Krian which implemented P5. Data was collected through in-depth interviews with teachers, school principals and observation of P5 activities. The research results show that the implementation of inclusive education in the P5 program faces a number of challenges, such as a lack of special training for teachers, limited resources, and a lack of understanding of students' special needs. However, this research also found opportunities including increased student engagement, development of social and emotional skills, and a more inclusive and welcoming learning environment for all students. In conclusion, despite the obstacles, the P5 program in the Merdeka Curriculum has great potential to support inclusive education at SD Muhammadiyah 1 Krian, provided there is adequate training policy support for educators, and active participation from all stakeholders. Inclusive education in elementary schools has challenges that must be faced, but it also provides opportunities to create a more inclusive environment and develop the potential of students with special needs. Continuous efforts are needed from all relevant parties to create a more inclusive education system and provide equal opportunities for all students to achieve quality education.